Managing Classical Islamic Text Literacy Acceleration through Triple Supervisor Small Group Model in Pesantren - Zainal Abidin; Ahmad Qusairi; Ikmal Wahyudi (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2026)
The decline in yellow-book literacy skills at the elementary level is a serious challenge for Islamic boarding schools. This study aims to analyze the strategy of organizing intensive learning to reduce the number of novice students reading the book at the Darullughah Wadda'wah Islamic Boarding School. Using a descriptive qualitative approach, this study examines the Ta'lim al-Muta'allim book guidance program in seven classes of fourth-grade elementary school students. Data were collected through participant observation, in-depth interviews with the Department of Education, and a documentary study of evaluation results. The research findings indicate that the "Triple Supervisor-Small Group" strategy is a key factor in the program's success. By dividing the class into small groups accompanied by three supervisors alternately, the quality control of the guidance becomes more precise. The high intensity of meetings (5x a week) with an effective duration of 45 minutes has been proven to be able to form a reading habit and accelerate mastery of the "Crucial Chapters" of Arabic grammar. Although the success rate has not reached 100% due to differences in individual learning speeds, the evaluation results show significant progress from the category of unable to read independently. Multi-layered supervisory management and routine monthly evaluation meetings are crucial quality assurance instruments. This research highlights the importance of human resource organization and time efficiency in Islamic boarding school curriculum management to accelerate the literacy skills of novice students in classical texts.